MEDICINAL PROPERTIES OF LAVENDER - LAVANDULA ANGUSTIFOLIA - Safarova Zakiya Teshayevna (Web of Journals Publishing, 2025)
The article describes the medicinal properties and use of Lavender products for aromatherapy. Use of oils, above-ground parts of the plant. The biology of the plant is described.
Keywords: Lavender, chemical, natural, health, man-made, factor, linalool, lavandulol and cameron, aromatherapy.